2006
DOI: 10.1017/s1355617706060024
|View full text |Cite
|
Sign up to set email alerts
|

Response bias and aging on a recognition memory task

Abstract: Response bias reflects the decision rule an individual uses when faced with uncertainty on recognition memory tasks. Recent studies indicate frontal regions may mediate response bias performance. One theory of aging also implicates frontal lobe contributions in age-related cognitive changes. This suggests that frontal lobe changes may mediate response bias in older adults. Consistent with this frontal aging hypothesis, we predicted that response bias would become more liberal with age. Methods: Participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
46
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 55 publications
3
46
3
Order By: Relevance
“…There was an effect of age found only in the most educated group, where the older participants used a more conservative criterion for responding. Huh et al (2006) found that increasing age correlated with an increasingly liberal response bias in older adults (aged 75-89), but not in a younger (aged 35-49) age cohort.Impaired discrimination in AD patients has been well documented, but there have been fewer studies exploring response bias in AD. In one such study, Balota, Burgess, Cortese, and Adams (2002) found patients with mild AD demonstrated a more liberal response bias to high frequency words than to low frequency words.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…There was an effect of age found only in the most educated group, where the older participants used a more conservative criterion for responding. Huh et al (2006) found that increasing age correlated with an increasingly liberal response bias in older adults (aged 75-89), but not in a younger (aged 35-49) age cohort.Impaired discrimination in AD patients has been well documented, but there have been fewer studies exploring response bias in AD. In one such study, Balota, Burgess, Cortese, and Adams (2002) found patients with mild AD demonstrated a more liberal response bias to high frequency words than to low frequency words.…”
mentioning
confidence: 81%
“…There was an effect of age found only in the most educated group, where the older participants used a more conservative criterion for responding. Huh et al (2006) found that increasing age correlated with an increasingly liberal response bias in older adults (aged 75-89), but not in a younger (aged 35-49) age cohort.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Although response bias is not generally characterized as representing a trait in the recognition literature, studies have identified a number of populations exhibiting a more liberal response bias than appropriate comparison groups, such as the elderly (e.g., Huh, Kramer, Gazzaley, & Delis, 2006), patients with Alzheimer's disease (e.g., Beth, Budson, Waring, & Ally, 2009), schizophrenia patients (e.g., Moritz, Woodward, Jelinek, & Klinge, 2008), dementia patients (e.g., Woodard, Axelrod, Mordecai, & Shannon, 2004), individuals with mental retardation (Carlin et al, 2008), and panic disorder patients (Windmann & Krüger, 1998). The association of liberal response bias and particular populations is consistent with the idea that groups of individuals may be differentiated from one another on the basis of response bias without a specific experimental intervention, which is, in turn, consistent with the notion of response bias as a cognitive trait.…”
mentioning
confidence: 99%
“…Because frontal brain regions are often implicated in criterion setting (see, e.g., Kramer et al, 2005), Huh et al (2006) correlated response bias on a recognition test with performance on four measures of executive function in 293 adults ranging from 35 to 89 years old. Among these measures, inhibition (indexed via a Stroop task) was the only significant predictor of response bias (r 0 .31, estimated from the reported beta values); Huh et al declared the analysis inconclusive.…”
mentioning
confidence: 99%